PENGGUNAAN FILLER ARANG KAYU PADA ASPAL LATASTON DAN ASPAL LASTON - Muhamad Fatkhur Rohman; Akhmad Hasanuddin; Luthfi Amri Wicaksono (JURNAL SIMETRIK, 2020)
The road pavement structure has a fillercommonly referred to as a filler. Filler (filler) is one of the materials that has an important function, namely as a cavity filler from the asphalt mixture. This research is to see the effect of adding wood charcoal filler content in AC-WC mixture and HRS-WC mixture with variations in the addition of wood charcoal by 0%; 0.5%; 1%; 1.5%; 2% based on total mixture. Examination of aggregate and asphalt was carried out to get the optimum level of asphalt, the optimum value of asphalt AC-WC was 5.30% and for a mixture of HRS-WC 7.89%. The AC-WC mixture obtained the Marshall Test value, obtained the optimum stability value of 1511.9 kg at the addition of 0% filler and decreased with the addition of 0.5%, 1%, 1.5%, 2%. While the HRS-WC mixture also obtained the Marshall Test value obtained optimum stability value of 1899.17 kg at 0% filler addition anddecreases at the addition of 0.5%, 1%, 1.5%, 2%.